Euroregions as Actors of World Politics - I. A. Budanova (Vestnik MGIMO-Universiteta)
The article analyses some problems connected with actorness of Euroregions. The author gives a brief review of the main Euroregions characteristics and their interrelations with the EU and nation-states. The article concludes that development of cross-border regions “abilities” promotes their actorness in the European space.